Burgen in umstrittenen Landschaften Eine Studie zur Entwicklung und Funktion von Burgen im südlichen Jütland (1232-1443) - Magnussen, Stefan (Sidestone Press, 2019)
Castles had a lasting influence on the practice of reign during the high and late Middle Ages throughout Europe. While this has received considerable attention for many regions, southern Jutland has not yet been perceived as a castle landscape neither by regional historians nor by castle research, although toponyms such as Sønderborg, ramparts like Tørning and palaces such as Gottorf, whose origin goes back to a medieval castle, still provides a vivid impression of the once important role played by such castles. From 2014 to 2018, the author conducted a research project at Kiel University on this phenomenon. With this book, he now presents the first comprehensive study of the castles between Eider and Kongeå, which have received little attention so far. On a micro-level, information on the individual structures on both sides of the German-Danish border from various disciplines such as history and medieval archaeology is compiled, critically evaluated and interconnected. The individual case studies are then placed in their spatial and historical contexts on a micro-level. The work is primarily inspired by the latest trends in international castle research, which emphasize the social complexity, landscape embedding and functional diversity of castles. Especially an innovative classification into different function types allows for completely new methodological approaches to the castles of this region. The book illustrates a total of seven evolutionary phases of this historical castle landscape, from the humble beginnings of the 12th century to the manorially complex and diverse structures of the 15th century. While it is evident that each of these 58 verifiable castles must be examined individually, they can only be meaningfully understood within their historical and landscape contexts. The volume thus sees itself as an important contribution to a more differentiated understanding of this complex territory, providing a frame of reference for further investigations and establishing the region as a castle landscape in supra-regional research.